2011
DOI: 10.1002/cjoc.201180251
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Theoretical and Experimental Studies on the CF3H Fire‐extinguishing Mechanism

Abstract: In order to clarify the chemical suppression mechanisms of CF3H, experimental and theoretical studies were conducted respectively in this paper. Firstly, the combustion species in low pressure laminar premixed flat methane flames with CF3H addition is measured by synchrotron radiation molecular beam mass spectrometry (SR‐MBMS) experimentally. Fire suppression chemistry of CF3H is investigated by selective detection of combustion radicals and intermediates in experimental process. Secondly, quantum chemistry ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…F∙ radicals can also capture H∙ radicals, but their ability is much worse than that of CF 3 ∙ radicals. The detailed kinetic study of CF 3 ∙ has been reported in a previous study [32], so it is not be discussed here. Each N(CF 2 CF 3 ) 3 molecule can produce at most three CF 3 ∙ radicals, which can also be inferred from its good fire‐extinguishing ability.…”
Section: Resultsmentioning
confidence: 99%
“…F∙ radicals can also capture H∙ radicals, but their ability is much worse than that of CF 3 ∙ radicals. The detailed kinetic study of CF 3 ∙ has been reported in a previous study [32], so it is not be discussed here. Each N(CF 2 CF 3 ) 3 molecule can produce at most three CF 3 ∙ radicals, which can also be inferred from its good fire‐extinguishing ability.…”
Section: Resultsmentioning
confidence: 99%
“…As an effective component for chemical extinguishment, , the CF 3 H molecule can react with hydroxyl and hydrogen radicals through hydrogen atom abstraction by radicals with negligible energy barriers of 1.102 and 8.134 kcal·mol –1 , respectively, leading to the generation of CF 3 • radicals (paths 15 and 16 in Figure S14). After that, the CF 3 • radical could spontaneously combine with a H • radical without any barrier, resulting in the formation of the CF 3 H product that has obviously lower energy than reactants (path 17 in Figure S14).…”
Section: Resultsmentioning
confidence: 99%
“…There have been many attempts in the literature to develop approaches that address the HF generation mechanism during fire suppression. The main emphasis of available researches are focused on HF yield amount [15] and mechanism of CF 3 H [16], thermal decomposition mechanism of CHF 2 CF 3 [17,18] and other Halon alternatives [19], HF production of CF 3 CHFCF 3 [20], thermal decomposition of trans-CF 3 CH = CHCF 3 [21], HF pyrolysis of CF 2 H 2 [22], thermal decomposition of CF 3 CBrH = CH [23] and so on. Although the yield of corrosive gases has been reported to impact potential damage on the surface of materials [24], the comprehensive study of the influence of HF on the color change of wooden materials is still unavailable.…”
Section: Introductionmentioning
confidence: 99%